2012
DOI: 10.1007/s00023-012-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Absolutely Continuous Spectrum for Random Schrödinger Operators on Tree-Strips of Finite Cone Type

Abstract: Abstract. A tree-strip of finite cone type is the product of a tree of finite cone type with a finite set. We consider random Schrödinger operators on these tree strips, similar to the Anderson model. We prove that for small disorder the spectrum is almost surely, purely, absolutely continuous in a certain set.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…indicates that x is closer to the root of Γ than y. In this example (s xy ) is not a symmetric matrix, but in a related model it may be chosen symmetric (rooted trees of finite cone types associated with a substitution matrix S, see [Sad12]). In particular, real analyticity of the density of states (away from the spectral edges) in this model follows from our analysis (We thank C. Sadel for pointing out this connection).…”
Section: Introductionmentioning
confidence: 99%
“…indicates that x is closer to the root of Γ than y. In this example (s xy ) is not a symmetric matrix, but in a related model it may be chosen symmetric (rooted trees of finite cone types associated with a substitution matrix S, see [Sad12]). In particular, real analyticity of the density of states (away from the spectral edges) in this model follows from our analysis (We thank C. Sadel for pointing out this connection).…”
Section: Introductionmentioning
confidence: 99%
“…For small disorder in the bulk of the spectrum, localization and Poisson statistics appears in one and quasione dimensional systems [GMP, KuS, CKM, Lac, KLS] (except if prevented by a symmetry [SS3]) and is expected (but not proved) in 2 dimensions. Delocalization for the Anderson model was first rigorously proved on regular trees (Bethe lattices) [Kl] and had been extended to several infinitedimensional tree-like graphs [Kl,ASW,FHS,AW,KLW,FHH,KS,Sa2,Sa3,Sha]. Recently it was shown that there is a transition from localization to delocalization on normalized antitrees at exactly 2-dimensional growth rate [Sa4].…”
mentioning
confidence: 99%
“…potential) the existence of absolutely continuous spectrum at low disorder has only been shown for trees and treelike graphs 1 of infinite dimension with exponentially growing boundary. A lot of work has been done in extending Klein's original result, also in recent years, [ASW,AW1,AW2,FHS1,FHS2,FHS3,FHH,Ha,KLW,KlS,Sa,Sh]. At large disorder and on the edge of the spectrum one typically finds Anderson localization (pure point spectrum) in any dimension [A, AM, CKM, DK, DLS, FMSS, FS, Klo, W].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%